Biomass torrefaction: properties, applications, challenges, and economy. (November 2019) - Niu, Yanqing; Lv, Yuan; Lei, Yu; Liu, Siqi; Liang, Yang; Wang, Denghui; Hui, Shi'en
Abstract: Biomass accounts for the largest renewable energy in the world, whereas its inherent drawbacks, such as low energy and mass density, hydrophilicity, poor grindability and severe ash-related issues, inhibit its extensive utilization. Torrefaction, conducted at 200–300 °C in an inert atmosphere, successfully overcomes the abovementioned drawbacks and improves the biomass applications. Thus, a critical review is performed for the new insight into further study, involving the properties improvement of torrefied biomass, applications on combustion and gasification, as well as the intractable challenges of ash-related issues during thermal conversion and economy viability. Compared to torrefaction duration and the moisture and size of biomass, the torrefaction temperature has the strongest impact on the biomass properties improvement. Respecting physical properties (energy density and grindabilty) and chemical thermal conversion characteristics, there exists an optimal torrefaction temperature at approximate 250 °C. Biomass torrefaction is strongly dependent on the degradation of hemicellulose. Herbaceous residues possess a higher degradation ratio compared to ligneous biomass; Besides, deciduous trees mainly containing xylan in hemicellulose are more active than coniferous trees which mainly contain glucomannan in hemicellulose. The torrefied biomass possesses increased carbon content, decreased H/C and O/C ratios, increased mass energy density, similar chemical compositions with coal, and the availability for gasification and co-firing. Moreover, large amount of Cl, S, and K release during torrefaction, which bring considerable fringe benefits by reduction or elimination of the intractable ash-related issues during thermal conversion, such as slagging, agglomeration and corrosion. At present, the cost of biomass torrefaction is higher than coal. However, it can be significantly reduced by the implementation of carbon credits market, increasing torrefaction plant equipment size, and empirical cumulation. Later, more attention should be focused on application demonstration and systematic economic optimization. Highlights: Torrefaction improves the biomass properties, applications, and economy significantly. Temperature and hemicellulose have primary effect on biomass properties improvement. Torrefaction improves syngas quality and increases cold gasification efficiency. Releases of Cl, S and K in torrefaction ease ash-related issues during thermal conversion. Application demonstrations on combustion and gasification of torrefied biomass are urgent.